Surfactant-polymer flooding in sandstones evaluated by computed tomography : Injeção de surfactante-polímero em arenitos avaliada com tomografia computadorizada - Tapias Hernández, Fabián Andrés, 1991- (2018)
Orientador: Rosangela Barros Zanoni Lopes Moreno